Momago - Rismawati Rismawati; Isbon Pageno (Universitas Muslim Maros, 2020)
When humans experience various difficulties in life, including illness, then they will try to find a cure for the disease, through medical treatment, then traditional treatment after being unsuccessful with medical treatment. But there are also those who directly use traditional medicine in accordance with local beliefs. This article explores beliefs and cultural practices of tau taa wana in the treatment of diseases through momago, a traditional ritual healing practiced in Uempanapa Village. This study was conducted in Uempanapa Village, Bungku Utara Subdistrict, North Morowali District, considering that tau ta'a wana (ta'a wana people) in this village still practices momago (a healing ritual) which is commonly held once a year. Using qualitative approach, data was collected using in-depth interview and observation techniques. Eleven participants involved in this study, they are varied on the basis of sex (eight men, and three women), age (between 42 and 72 years), and position [three shamans (dukun), a drum beat (to paganda), a gong drummer (to myingko gong), a dancer (to motaro), patient (to ongoyo), and three patients’ family (to mongoyo). Momago is a traditional healing ritual using supernatural power mediated by shamans (walia). This healing ritual is based on a belief in supernatural beings that are considered to play role in causing various diseases. Momago is practiced by tau taa wana and this is not only practiced when there are calls from residents to treat their sick relatives, but they are also often performed at large events such as the reception of important guests, cultural arts festivals, and so forth. They believe that patients will recover after ancestral spirits entering one’s body. In this healing ritual, tau taa wana is carried out by utilizing supernatural power, through which walia repeatedly calls the spirit. This healing ritual is usually carried out at night and takes up to three weeks, depending on the type of disease and the number of patients. The types of diseases that are cured through momago include witchcraft (fofongontau/doti), trance (pasuak), rebuke (katrapes), crazy (fando) and drowning (mlondong), kinds of illnesses which believed to be personalistic diseases. It is also believed that the success of a ritual is marked by the number of momago participants who have possessed spirits, the more they are, the more successful the treatment has been. Although not all diseases can be cured through momago, and not all sick people treated through momago can recover from their illness, momago is still practiced because it has become a hereditary tradition from their ancestors and/or because of the requests from patients’ family.